Prevention of Respiratory Syncytial Virus Infection in Healthy Adults by a Single Immunization of Ad26.RSV.preF in a Human Challenge Study. (5th January 2021) - Sadoff, Jerald; De Paepe, Els; DeVincenzo, John; Gymnopoulou, Efi; Menten, Joris; Murray, Bryan; Rosemary Bastian, Arangassery; Vandebosch, An; Haazen, Wouter; Noulin, Nicolas; Comeaux, Christy; Heijnen, Esther; et al.
Abstract: Background: Respiratory syncytial virus (RSV) is a significant cause of severe lower respiratory tract disease in children and older adults, but has no approved vaccine. This study assessed the potential of Ad26.RSV.preF to protect against RSV infection and disease in an RSV human challenge model. Methods: In this double-blind, placebo-controlled study, healthy adults aged 18–50 years were randomized 1:1 to receive 1 × 10 11 vp Ad26.RSV.preF or placebo intramuscularly. Twenty-eight days postimmunization, volunteers were challenged intranasally with RSV-A (Memphis 37b). Assessments included viral load (VL), RSV infections, clinical symptom score (CSS), safety, and immunogenicity. Results: Postchallenge, VL, RSV infections, and disease severity were lower in Ad26.RSV.preF (n = 27) vs placebo (n = 26) recipients: median VL area under the curve (AUC) quantitative real-time polymerase chain reaction: 0.0 vs 236.0 ( P = .012; predefined primary endpoint); median VL-AUC quantitative culture: 0.0 vs 109; RSV infections 11 (40.7%) vs 17 (65.4%); median RSV AUC-CSS 35 vs 167, respectively. From baseline to 28 days postimmunization, geometric mean fold increases in RSV A2 neutralizing antibody titers of 5.8 and 0.9 were observed in Ad26.RSV.preF and placebo, respectively. Ad26.RSV.preF was well tolerated. Conclusions: Ad26.RSV.preF demonstrated protection from RSV infection through immunization in a human challenge model, and therefore could potentially protect against natural RSV infection and disease. Clinical Trials Registration: NCT03334695; CR108398, 2017-003194-33 (EudraCT); VAC18193RSV2002. Abstract : Ad26.RSV.preF, an investigational vaccine against Respiratory Syncytial Virus (RSV) was evaluated in an RSV human challenge model. Vaccinated individuals showed a reduction in infections, viral load and disease severity compared to placebo. Ad26.RSV.preF warrants further investigation in field efficacy studies.